PENGARUH KOMITMEN ORGANISASI, ORIENTASI BERP RESTASI DAN EFFORT PADA KINERJA JABATAN DAN KEPUASAN KERJA - Nurchasanah,, Siti; Triyono, Triyono; Mardalis, Ahmad (Jurnal Manajemen Dayasaing, 2014)
The objective of this study is to analyze the inï¬‚uence of organizational commitment, achievement orientation and effort on job performance and job satisfaction. The total sample of 80 employees of PT Perkebunan Nusantara V (Persero) with purposive sampling. Based on the data analysis can be concluded that organizational commitment inï¬‚uences the job performance, as well as achievement orientation, achievement orientation inï¬‚uences the job performance. Meanwhile, the Effort does not have signiï¬cantly on the job performance. This is because at that time of the study of human resource management system associated with the consequence of Effort which has not been implemented. This condition is also inï¬‚uenced by individual effort which has not reï¬‚ected the effort from all job performances, remembering job performance results obtained from group performance subvention. Organizational commitment signiï¬cantly has greater signiï¬cantly on job performance than achievement orientation. This study also found that job performance has inï¬‚uence on job satisfaction and job satisfaction has inï¬‚uence on organizational commitment.